2019
DOI: 10.1016/j.scitotenv.2019.133726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the process performance and microbial community by addition of the metabolic uncoupler 3,3′,4′,5-tetrachlorosalicylanilide in sequencing batch reactors

Abstract: A complete study about the effects of 3,3',4',5-tetrachlorosalicylanilide (TCS) on organic matter elimination performance, sludge production and on the microbial community of a biological wastewater treatment process has been performed. For this purpose two sequencing batch reactors (SBR) worked in parallel for 43 days with 0.8 mg•L -1 of TCS (SBR-1) and without this metabolic uncoupler (SBR-2). Results indicated that 63.3% of sludge reduction was achieved in SBR-1. However, COD removal efficiency was maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…However, a significant increase (p < 0.05, in Duncan's tests) in the relative abundance of Bacteroidetes, Gammaproteobacteria and Firmicutes over Actinobacteria and Alphaproteobacteria occurred immediately after the pNP addition (Figure 6a). Similar to our study, Ferrer-Polonio et al [37] reported the dominance of Proteobacteria (all classes) in an SBR after the addition of the metabolic uncoupler TCS. These authors also reported an increase in the relative abundance of Gammaproteobacteria, although the opposite trend compared to this study was reported regarding Alphaproteobacteria.…”
Section: Effect Of Pnp On Bacterial Community Structure During Operation Of the Mbrsupporting
confidence: 92%
“…However, a significant increase (p < 0.05, in Duncan's tests) in the relative abundance of Bacteroidetes, Gammaproteobacteria and Firmicutes over Actinobacteria and Alphaproteobacteria occurred immediately after the pNP addition (Figure 6a). Similar to our study, Ferrer-Polonio et al [37] reported the dominance of Proteobacteria (all classes) in an SBR after the addition of the metabolic uncoupler TCS. These authors also reported an increase in the relative abundance of Gammaproteobacteria, although the opposite trend compared to this study was reported regarding Alphaproteobacteria.…”
Section: Effect Of Pnp On Bacterial Community Structure During Operation Of the Mbrsupporting
confidence: 92%
“…The phenomenon of uncoupled metabolism may be carried out under abnormal conditions such as the presence of inhibitory compounds or some heavy metals. The use of uncouplers are to reduce sludge production, control microbial contamination and increase substrate removal efficiency (Ferrer-Polonio et al, 2019).…”
Section: Metabolic Uncouplersmentioning
confidence: 99%
“…Proteobacteria, Firmicutes, Fusobacteria , and Tenericutes made up 72.4 % of the overall bacterial population. As a result, sludge reduction owing to TCS addition could be attributed to both the uncoupling effect and cellular lysis 181. In a related study, metabolic uncoupling and energy distribution were found to be important factors in TCS‐induced sludge reduction.…”
Section: Sludge Reduction Mechanisms In Sbr Systemsmentioning
confidence: 99%
“…where the chemical formulas of the cell and electron donor are The uncoupled metabolism phenomenon is promising because it can be quickly fed into a WWTP's aeration tank, eliminating the need for modification [180]. This can be done in unusual circumstances such as (i) presence of toxic compounds, (ii) when temperatures are not ideal, (iii) at limited nutrients, (iv) presence of oxic-anoxic cycling conditions, and (v) presence of chemical uncouplers [181].…”
Section: Sludge Reduction Mechanisms In Sbr Systemsmentioning
confidence: 99%